2006
DOI: 10.7498/aps.55.2977
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of crystal lattice constant and strain of GaN epilayers with different AlxGa1-xN and AlN buffer layers grown on Si(111)

Abstract: Hexagonal GaN epilayers with different AlxGa1-xN and AlN buffer layers were grown on Si(111) by metal-organic vapor phase epitaxy (MOVPE). Under the same growth conditions, the sample with four AlxGa1-xN buffer layers and one AlN buffer layer were grown on Si(111). According to the results of Rutherford backscattering (RBS)/channeling along axis, the conventional θ—2θ scans normal to GaN(0002) and (1122) plane at 0° and 180° azimuthal angles, and the reciprocal-space X-ray mapping (RSM) on GaN(1015) plane, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, for GaN heteroepitaxy on Si substrate, the large lattice mismatch and thermal mismatch between GaN and Si usually lead to high threading dislocation (TD) density and the formation of cracks in GaN layer during the cooling process. [3] Up to now, various interlayers (ILs) such as AlN IL, [4−6] AlN/GaN superlattice [7,8] and AlGaN ILs, [9−13] have been introduced into the growth of GaN epilayer to compensate the tensile stress and prevent the formation of cracks. Previously, we have reported that AlGaN IL plays a remarkable role in introducing compressive strain into the subsequently grown GaN layer and significantly reducing TD density in the GaN epilayer.…”
Section: Introductionmentioning
confidence: 99%
“…However, for GaN heteroepitaxy on Si substrate, the large lattice mismatch and thermal mismatch between GaN and Si usually lead to high threading dislocation (TD) density and the formation of cracks in GaN layer during the cooling process. [3] Up to now, various interlayers (ILs) such as AlN IL, [4−6] AlN/GaN superlattice [7,8] and AlGaN ILs, [9−13] have been introduced into the growth of GaN epilayer to compensate the tensile stress and prevent the formation of cracks. Previously, we have reported that AlGaN IL plays a remarkable role in introducing compressive strain into the subsequently grown GaN layer and significantly reducing TD density in the GaN epilayer.…”
Section: Introductionmentioning
confidence: 99%
“…However, for GaN heteroepitaxy on Si substrate, the large lattice mismatch and thermal mismatch between GaN and Si usually lead to high threading dislocation (TD) density and the formation of cracks when cooling down to room temperature from the growth temperature. [3] Up to now, various interlayers (ILs) such as AlN IL, [4−6] AlN/GaN superlattice [7,8] and step-graded or composition-graded AlGaN IL, [9−13] have been introduced into the growth of GaN epilayer to compensate for the large thermal tensile stress and prevent the formation of cracks. Among these ILs, AlN IL reduces the crack density and concurrently introduces extra edge-type TDs in the top GaN films, AlN/GaN superlattice or step-graded AlGaN IL growth needs a precise control of layer parameters and is very much dependent on the experimental system.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, In x Ga 1−x N/GaN multi-quantum wells (MQWs) have been attracting much research interest, acting as active layers in high brightness III-nitride laser emitting diodes (LEDs) and cw blue-green laser diodes. [1,2] In x Ga 1−x N/GaN heterostructures can exhibit intense photoluminescence (PL) despite a high density of dislocations and defects. [3] A great deal of research effort has been focused on In x Ga 1−x N/GaN MQWs structures.…”
mentioning
confidence: 99%